Understanding Pat Conroy - Seltzer, Catherine (Understanding contemporary American literature, 2015)
"Pat Conroy's work as a novelist and a memoirist has indelibly shaped the image of the American South in the cultural imagination. His writing has rendered the physical landscape of the South Carolina lowcountry familiar to legions of readers, and it has staked out a more complex geography as well, one defined by domestic trauma, racial anxiety, religious uncertainty, and cultural ambivalence. In Understanding Pat Conroy, Catherine Seltzer engages in a sustained consideration of Conroy and his work. The study begins with a sketch of Conroy's biography, a narrative that, while fascinating in its own right, is employed here to illuminate many of the motifs and characters that define his work and to locate him within southern literary tradition. The volume then moves on to explore each of Conroy's major works, tracing the evolution of the themes within and among each of his novels, including The Great Santini, The Lords of Discipline, The Prince of Tides, Beach Music, and South of Broad, and his memoirs, among them The Water Is Wide and My Losing Season. Seltzer's insightful close readings of Conroy's work are supplemented by interviews and archival material, shedding new light on the often-complex dynamics between text and context in Conroy's oeuvre. More broadly Understanding Pat Conroy also explores the ways that Conroy delights in troubling the boundaries that circumscribe the literary establishment. Seltzer links Conroy's work to existing debates about the contemporary American canon, and, like Conroy's work itself, Understanding Pat Conroy will be of interest to his readers, students of American literature, and new and veteran South watchers"--